Grhagaṇitabōdhāmrtamu : prācīna vāstugrandhamulanuṇḍi sañgrahimpambaḍina - Ĉallālakṣmīnarasiṃhaśāstri (Śrī Lakṣmīnarasiṃha Pres, 1978)
Astrological and astronomical calculations for building construction.